The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1590/s1415-47572000000100029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phaseolus vulgaris QTL in controlling host-bacteria interactions under two levels of nitrogen fertilization

Abstract: ported that photoperiod influences the expression of CBB, with susceptible tropical genotypes showing a higher level of resistance when grown under sub-tropical conditions. So far, the effect of nitrogen on the phenotypic expression of resistance genes of Phaseolus to Xanthomonas has not been studied. This is an important area of research, since in tropical areas common beans are cultivated under a variety of geographic and technological conditions which affect the amount of nitrogen available to both host and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 17 publications
2
7
0
3
Order By: Relevance
“…Quantitative trait locus (QTL) analysis is a powerful approach for understanding genetic variation and mechanisms of host participation in symbiotic interactions. QTLs related to BNF have been identified in several legumes, including pea (Bourion et al, 2010), Lotus japonicas (Tominaga et al, 2012), and common bean (Phaseolus vulgaris; Tsai et al, 1998;de Souza et al, 2000). At present, few QTLs controlling nodulation traits in soybean have been described.…”
Section: Increasing Nodule Size1 Expression Is Required For Normal Rhmentioning
confidence: 99%
“…Quantitative trait locus (QTL) analysis is a powerful approach for understanding genetic variation and mechanisms of host participation in symbiotic interactions. QTLs related to BNF have been identified in several legumes, including pea (Bourion et al, 2010), Lotus japonicas (Tominaga et al, 2012), and common bean (Phaseolus vulgaris; Tsai et al, 1998;de Souza et al, 2000). At present, few QTLs controlling nodulation traits in soybean have been described.…”
Section: Increasing Nodule Size1 Expression Is Required For Normal Rhmentioning
confidence: 99%
“…Isso indica que essas características fenotípicas são controladas por QTL estreitamente ligados ou pela ação de um único QTL com efeito pleiotrópico (Lebreton et al, 1995;Loudet et al, 2003). QTL com efeitos pleiotrópicos já foram observados em vários caracteres morfológicos e de desenvolvimento na soja e no feijoeiro (Keim et al, 1990;Mansur et al, 1993;Nodari et al, 1993;Souza et al, 2000;Nicolás et al, 2006). A maior dificuldade que se apresenta diante desse tipo de interações consiste em distinguir QTL fortemente ligados, que afetam várias características, de um único QTL com efeitos pleiotrópicos.…”
Section: Marcadores Associados Com O Crescimento Da Planta E a Nodulaçãounclassified
“…There have been a few QTL studies on genetic determinants for nodule traits, mainly for nodule number per plant, and to a lesser extent, for nodule biomass and nodule area (Nodari et al, 1993;Souza et al, 2000;Nicolás et al, 2006;Bourion et al, 2010). Bourion et al (2010) identified nine different genomic regions controlling nodule development and growth on pea (Figure 9).…”
Section: A Improving the Efficiency Of The Legume-rhizobiamentioning
confidence: 99%